KAJIAN KUALITAS AIR TERHADAP PERTUMBUHAN RUMPUT LAUT (GRACILARIA VERRUCOSA) DI TAMBAK DENGAN METODE VERTIKULTUR - Ruslaini Ruslaini (Universitas Muhammadiyah Makassar, 2016)
The growth of seaweed (Gracilaria verrucosa) is influenced by environmental conditions such as light intensity, temperature, salinity, pH, nitrates, phosphates. This study aims to identify factors that affect water quality seaweed growth, and analyze the relationship between water quality factors with the growth of seaweed. The study was conducted from August to October 2016. The results showed the specific growth of seaweed during the study an average of 3.605 %. Water quality during the study, the average light intensity 2311.5 lux, average temperature 27°C, the average pH 7.92, average salinity 18.85 ppt, nitrate average of 0.2253 mg/L and phosphate average of 0.380 mg/L. Water quality is obtained during the study supports the growth of seaweed.